EP 111. Phase-locking analysis of EEG-data in movement related tasks reveals functional network of synchronous activity. Issue 9 (September 2016) - Rosjat, N.; Popovych, S.; Wang, B.; Liu, L.; Tóth, T.I.; Abdollahi, R.; Viswanathan, S.; Grefkes, C.; Fink, G.R.; Daun-Gruhn, S.
Abstract : The performance of motor actions is a highly complex task where the movement of different body parts has to be coordinated by the activity of various brain regions. In particular, the interplay of brain regions of the motor cortex is crucial. In the study presented here, the interaction of different motor related brain regions during simple internally and externally initiated finger movements was investigated during preparation and execution of those movements. To this end, EEG data (64 channel system) were recorded from 18 right-handed healthy participants (22–35 years, 10 female). The participants performed a finger tapping paradigm that contained left and right index finger movements which were triggered either by a visual cue or by voluntary choice. We carried out inter-regional phase-locking analysis of Morlet wavelet phases in delta-theta (2–7 Hz), alpha (8–12 Hz) and beta (13–30 Hz) frequency bands of the Laplacian referenced EEG data in order to identify coupling between brain regions during the motor task. We analyzed connectivity in a network involving electrodes lying above the premotor areas (PM: FC3, FC4), the supplementary motor areas (SMA: Cz, FCz) and the primary motor cortex (M1: C3, C4) as nodes. We found significant changes of synchronization in the delta-theta frequency band during both movement preparation and execution. The construction of lateralization networks revealed that the phase-locking effect in these frequency bands was stronger for connections from motor regions to supplementary motor areas contralaterally to the moving hand than on the ipsilateral side. The interregional synchronizations appeared only when both regions showed strong intraregional phase locking. Thus, intraregional phase locking in the delta-theta frequencies seems to be a prerequisite for interregional phase locking. We hypothesize that both intra- and interregional phase locking form a functional network of synchronous activity. This activity enhances the excitability of the motor system so that transient cue signals are able to induce different kinds of movements during movement preparation. Additionally we found strong synchronization in the beta-frequency band that appeared after the movement has been executed for connections from the supplementary motor areas to the primary motor cortex and the pre-motor cortex contralaterally to the moving hand. Since this synchronization effect is expressed significantly stronger during the self-initiated than during visually-triggered finger movements, we suggest that it might be related to the suppression of the internal "go" cue after the movement was executed.